AMOR DEI INTELLECTUALIS. VERNUNFT-UND GOTTESLIEBE IN GIPFELSÄTZEN NEUZEITLIECHER SYS-TEMBILDUNGEN (SPINOZA, HEGEL, SCHELLING, FICHTE) - Janke, Wolfgang (Daimon Revista Internacional de Filosofia, 1994)
There is a remarcable fact concerning the history of modern philosophy. The axiom since Spinoza runs: Love («amor Dei intellectualis», «absolute Liebe», «Wille de Liebe») , not reason («Vernunft», «Geist», «Reflexion») ist the first principle, which unifies alls beings.The first divison of our inquiry explains this principle within of the systems from Spinoza to Schelling in a critical way. The second part resumes the same axiom amongs Fichte's philosophy of religion and reintroduces it as the real principle of human speculation.